Hipomineralização molar-incisivo, fluorose e cárie dentária em áreas com diferentes concentrações de flúor na água - Fernandes, Igor Cartaxo (2019)
Introduction: Changes in tooth enamel are common findings, Among them we have conditions related to development as molar-incisive hypomineralization and dental fluorosis, as well as acquired conditions such as dental caries. Incisor molar hypomineralization (MIH) is a qualitative alteration in dental enamel development that affects the first permanent molars and may in some cases extend to the permanent incisors. Objective: To investigate the prevalence of MIH, fluorosis and dental caries in schoolchildren in rural areas of the Northeast of Brazil with different residual fluoride contents in water. Materials and Methods: This is a crosssectional investigation, carried out by means of an epidemiological, descriptive and analytical survey. The project was approved by the CCS/UFPB Human Research Ethics Committee (08812219.2.0000.5188). Initially, a mapping of fluoride concentrations was performed in the waters of schools in rural areas of the municipalities of the sertão in northeastern Brazil (São João do Rio do Peixe, Poço José de Moura, Marizópolis, Uiraúna). A census was made of schoolchildren enrolled regularly in the municipal education networks with ages ranging from 6 to 12 years and with all first permanent molars erupted, totaling 610 children. Parents/guardians answered questionnaires on socio-demographic data. The children answered questionnaires on access to dental services, oral hygiene habits. A dental surgeon was calibrated to assess dental fluorosis and incisor molar hypoplasia (Kappa = 0.73). Data were collected by clinical examination, observing the prevalence of MIH according to the criteria of the European Academy of Pediatric Dentistry, dental caries were analyzed in permanent and deciduous teeth according to the recommendations of the World Health Organization (WHO), and the prevalence of dental fluorosis was defined according to the index proposed by Thylstrup and Fejerskov. Mothers of children with MIH were invited to an interview on aspects inherent to the period from gestation to the first years of the child's life. The descriptive analysis of the data was carried out using statistical software in the Statistical Package for the Social Sciences (software free version, SPSS/PC+, Inc.; Chicago, IL, USA), while the inferential analysis was carried out using chi-square tests, Fischer's exact and binary logistic regression for multivariate analysis, adopting for all tests one (IC=95%) and a value of p≤0.05 as significant. Results: The prevalence of MHI was 9.8% dental fluorosis was 38.5%. There was no significance among the independent variables: gender, age and concentration of fluoride in water in relation to the prevalence of MIH (p>0.05), as to severity it was observed that (58.3%) were mild and (41.7%) severe manifestations, the dental elements of the maxilla were more affected in relation to those of the mandible. It was observed that children with dental fluorosis had a greater predisposition to severe MIH lesions (p=0.010; OR=4.462; CI=1.373-17.494). Among the clinical findings of MIH, the most common were the opacities demarcated. The mean DMFT in children with MIH was 1.40 (±1.46) higher than 0.96 (±1.58) in children without MIH. Conclusion: The prevalence of MIH was 9.8%, dental fluorosis 38.5% and mean DMFT/dmft were 1,40 and 1,87, respectively. This study found that gender, age and fluoride concentrations do not influence the prevalence of MIH, however, children with MIH had a higher CPOD. Dental fluorosis, when present in children with MIH, was observed to be more severe in the clinical manifestations of MIH in dental elements.